Novel Homozygous PADI6 Variants in Infertile Females with Early Embryonic Arrest - Xu, Yao; Wang, Rongxiang; Pang, Zhi; Wei, Zhiyun; Sun, Lihua; Li, Sa; Wang, Guanghua; Liu, Yu; Zhou, Yiwen; Ye, Hongjuan; Jin, Liping; Xue, Songguo (Frontiers in Cell and Developmental Biology, 2022)
Early embryonic arrest denotes premature termination of development in pre-implantation embryos, which is one of the major phenotypes of recurrent assisted reproduction failure. Padi6 has been proven to be a member of subcortical maternal complex (SCMC) in mice, which is essential in oocyte maturation and embryogenesis. We and other groups previously found that biallelic mutations in PADI6 caused female infertility manifesting as early embryonic arrest. In this study, we identified two novel homozygous variants (p.Cys163Arg, and p.Trp475*) of PADI6 in two infertile patients from a cohort of 75 females with the phenotype of early embryonic arrest. In vitro expression study indicated severe decrease of PADI6, which might destruct the stability of SCMC. Our study expanded the mutational spectrum of PADI6, and further supported the causality between PADI6 mutations and female infertility.